2018
DOI: 10.1039/c8ra04205e
|View full text |Cite
|
Sign up to set email alerts
|

A review of the interfacial characteristics of polymer nanocomposites containing carbon nanotubes

Abstract: The state of research on the characteristics at the interface in polymer nanocomposites is reviewed. Special emphasis is placed on the recent advances in the fundamental relationship between interfacial characteristics and nanocomposite properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(109 citation statements)
references
References 401 publications
1
106
0
2
Order By: Relevance
“…For example, butyl groups are more effective in reducing interfacial thermal resistance compared to carboxyl and hydroxyl according to molecular dynamic simulation 266 . However, the covalent modification of the carbon surface induces the hybridisation from sp 2 to sp 3 reducing conjugated bonds and lowering its electrical properties 267 Depending on the stiffness of the polymer backbone, the aromatic conjugated polymer chains may create a helical wrap around the lateral side of the carbon nanotubes throughinteractions. The wrapping mechanism occurs when the number of polymer units interacting with the nanotube surface at the expense of some torsional energy necessary to distort are sufficient.…”
Section: Interfacial Bonding Between Filler and Polymer Matrixmentioning
confidence: 99%
“…For example, butyl groups are more effective in reducing interfacial thermal resistance compared to carboxyl and hydroxyl according to molecular dynamic simulation 266 . However, the covalent modification of the carbon surface induces the hybridisation from sp 2 to sp 3 reducing conjugated bonds and lowering its electrical properties 267 Depending on the stiffness of the polymer backbone, the aromatic conjugated polymer chains may create a helical wrap around the lateral side of the carbon nanotubes throughinteractions. The wrapping mechanism occurs when the number of polymer units interacting with the nanotube surface at the expense of some torsional energy necessary to distort are sufficient.…”
Section: Interfacial Bonding Between Filler and Polymer Matrixmentioning
confidence: 99%
“…In particular, nanocomposites not only have remarkable properties that can be tailored for broad application in many fields, but their processability is also simple. Nanocomposites could help the development of light-weight structural materials and functional materials (Park and Seo, 2012;Mittal et al, 2015;Chen et al, 2018;Mohan et al, 2018). One interesting possibility offered by functional nanocomposites is to exploit their piezoelectric response for structural health monitoring (SHM) (Pegoretti, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42] However, the carbon nanotube-polymer interface is oen weak and the long-range structure of the polymer segment is hard to control. 43 For example, a prior study demonstrated that one polymer could displace another on a SWNT surface. 44 The competitive binding between SWNTs and different polymers, along with the potential for the interpenetration of polymer layers, complicate the implementation of this strategy to construct ordered nanostructures comprised of multiple, self-sorted components.…”
Section: Introductionmentioning
confidence: 99%